2005
DOI: 10.1111/j.1742-4658.2005.04865.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient RNA ligation by reverse‐joined hairpin ribozymes and engineering of twin ribozymes consisting of conventional and reverse‐joined hairpin ribozyme units

Abstract: In recent years RNA has become the focus of development into new diagnostic and therapeutic schemes. Antisense-RNA, ribozyme, aptamer and siRNA technologies have been developed and have found application in molecular medicine [1][2][3][4][5][6][7]. Signalling aptamers and aptazymes have been constructed that can sense a number of molecules in real time and thus are valuable diagnostic tools [8][9][10]. Furthermore, recently discovered riboswitches that regulate gene expression in vivo in response to specific m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…This RNA thermodynamics-driven observation suggests that hairpin ribozymes, both as individual modules and in combined structures, could have catalyzed the synthesis of progressively longer RNA molecules from short and structurally simple modules. The ligase ability of hairpin ribozymes linked to other RNA molecules has been experimentally demonstrated by combining two ribozyme units into one functional twin molecule (Ivanov et al 2005). In any case, our in silico RNA folding study indicated that most ligation events yield molecules whose minimum free energy structure does not retain that of the two appended RNA modules.…”
Section: A Stepwise Model For the Origin Of The Rna Worldmentioning
confidence: 80%
“…This RNA thermodynamics-driven observation suggests that hairpin ribozymes, both as individual modules and in combined structures, could have catalyzed the synthesis of progressively longer RNA molecules from short and structurally simple modules. The ligase ability of hairpin ribozymes linked to other RNA molecules has been experimentally demonstrated by combining two ribozyme units into one functional twin molecule (Ivanov et al 2005). In any case, our in silico RNA folding study indicated that most ligation events yield molecules whose minimum free energy structure does not retain that of the two appended RNA modules.…”
Section: A Stepwise Model For the Origin Of The Rna Worldmentioning
confidence: 80%
“…Research in the field of chemical biology for example has afforded a variety of ribozymes with useful activities, artificial riboswitches, and diagnostic tools [1][2][3][4]. Our contribution to the field have been a number of RNA systems derived from the hairpin ribozyme that allow for controlled cleavage and ligation of suitable RNA substrates [5][6][7][8][9][10][11]. In particular, we have developed twin ribozymes for RNA repair and site-specific labeling [5][6][7][8], and aptazymes that are controlled by the oxidation state of the allosteric activator flavine mononucleotide [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Our contribution to the field have been a number of RNA systems derived from the hairpin ribozyme that allow for controlled cleavage and ligation of suitable RNA substrates [5][6][7][8][9][10][11]. In particular, we have developed twin ribozymes for RNA repair and site-specific labeling [5][6][7][8], and aptazymes that are controlled by the oxidation state of the allosteric activator flavine mononucleotide [9,10]. In the course of those studies, we also sought to develop a ribozyme that processes itself from a linear transcript to a cyclic RNA species [11].…”
Section: Introductionmentioning
confidence: 99%
“…Hairpin ribozymes that form a stable structure, such that fragments remain bound, favor ligation, whereas hairpin ribozymes that are less stable, such that cleavage fragments can easily dissociate, favor cleavage (Fedor 1999, Welz et al 2003. These characteristic features distinguish the hairpin ribozyme from other small ribozymes, and we have shown in previous work that structural manipulation of hairpin ribozyme variants allows tuning of cleavage and ligation activity (Welz et al 2003;Ivanov et al 2005;Vauleon et al 2005;Drude et al 2007Drude et al , 2011Pieper et al 2007;Müller 2013, Balke et al 2014). Among these variants is a hairpin ribozyme that can cleave off its 5 ′ -and 3 ′ -end (Pieper et al 2007).…”
Section: Introductionmentioning
confidence: 67%